Pemeriksaan Minuta Akta Notaris Untuk Kepentingan Penyidikan Dikaitkan Kewajiban Notaris Merahasiakan Akta - Livia Suha Putri; Habib Adjie (LPPM Universitas Ekasakti Padang, 2024)
A notary is a public official who has the authority to make authentic deeds regarding all acts, agreements and provisions required by statutory regulations and/or desired by interested parties. A deed made by a Notary can be used as strong evidence and the Notary needs to keep the contents of the deed he has made confidential. In carrying out their position, Notaries should be careful to avoid unlawful acts which can then be summoned by the judiciary. UUJN provides space for investigators to be able to examine Notarial deeds for investigative purposes as intended in Article 66 UUJN. The problem discussed is an examination of the minutes of Notarial deeds carried out by the Regional Notary Honorary Council for the purposes of investigations related to the principle of confidentiality and forms of protection for Notaries as public officials who are called upon to provide information. regarding the contents of the deed. The result obtained is that the Notary's obligation to keep the deed confidential as intended in Article 16 paragraph (1) letter f UUJN can be concluded as not violating the Principle of Notary Confidentiality. A Notary, in carrying out his official duties, is obliged to keep the contents of the deed and all information obtained by the Notary confidential in carrying out his official duties, unless statutory provisions order the Notary who is summoned as a witness to disclose this matter. keep the Notary's position confidential and fulfill his legal obligations as a witness in providing information regarding the contents of the deed as necessary. as evidence in court for law enforcement.